2006
DOI: 10.1007/s11274-005-9030-3
|View full text |Cite
|
Sign up to set email alerts
|

Mucor hiemalis: a new source for uricase production

Abstract: One hundred and sixty-five strains of microorganisms with the ability to grow in a medium containing uric acid as a major source of nitrogen were isolated from soil samples during a screening program. Among them, a zygomycete fungus with well-developed columellae was recognized to produce high levels of the enzyme in a short time. Classification of the isolated fungus was carried out according to the morphological and culture characteristics of the organism, and it was identified as Mucor hiemalis. The fungus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
19
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 27 publications
(24 reference statements)
9
19
0
4
Order By: Relevance
“…Acidic fermentation medium give higher production medium as compared to more basic fermentation medium. The result was coincided with those of Tohamy and Shindia [7] and Yazdi et al [5] who found that pH 6.0 was optimum pH medium for uricase production from Aspergillus flavus and Mucor hiemalis, respectively. However, this result is in disagreement by Ammar et al [8] which reported optimum pH for uricase by Aspergillus flavus was 9.2.…”
Section: A Effect Of Phsupporting
confidence: 90%
See 1 more Smart Citation
“…Acidic fermentation medium give higher production medium as compared to more basic fermentation medium. The result was coincided with those of Tohamy and Shindia [7] and Yazdi et al [5] who found that pH 6.0 was optimum pH medium for uricase production from Aspergillus flavus and Mucor hiemalis, respectively. However, this result is in disagreement by Ammar et al [8] which reported optimum pH for uricase by Aspergillus flavus was 9.2.…”
Section: A Effect Of Phsupporting
confidence: 90%
“…When the level of uric acid increases in blood over than the normal value it can cause renal failure and may contribute to a group of diseases such as gout, leukimia, toxemia of pregnancy, severe renal impairment and idiopathic calcium urate nephrolithiasis [4]. The first application of uricase in clinical biochemistry is as diagnostic reagents for measurement of uric acid in blood and other biological fluids [5]. Purified uricase from Asperfillus flavus has been found effective in the treatment of hyperuricemia and gout [6].…”
Section: Introductionmentioning
confidence: 99%
“…Uricase has been found in mammalian (Wu et al 1989), plant (Suzuki and Verma 1991), and microbial cells (Yazdi et al 2006;Lotfy 2008). Microorganisms, such as bacteria, yeast, and filamentous fungi, are important sources of uricase.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigators (Yazdi et al, 2006;Lotfy, 2008 ) studied the optimal temperature and pH for the production of uricase by microorganisms. The effect of various carbon and nitrogen sources on the formation of uricase by microorganisms was studied by several authors (Azab et al, 2005;Zhou et al, 2005;Yazdi et al, 2006;Lotfy, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of various carbon and nitrogen sources on the formation of uricase by microorganisms was studied by several authors (Azab et al, 2005;Zhou et al, 2005;Yazdi et al, 2006;Lotfy, 2008).…”
Section: Introductionmentioning
confidence: 99%